Peran Makanan Bergizi dalam Mencegah Stunting di SDN 7 Mataram, Nusa Tenggara Barat: Proyek Pembelajaran pada Mata Kuliah Agama Islam - Indrawan Eka Badri; Olfi Destika; Nurmutyah Naylah; Rozita; Hasri Finolah; Agus Kurnia (Bhakti: Jurnal Pengabdian Masyarakat, 2024)
Stunting is a chronic health problem that is still a concern in Indonesia, including in West Nusa Tenggara. One of the efforts to prevent stunting is to provide nutrition education to the community. This article describes community service activities carried out by Mataram University students through project-based learning in Islamic Religion courses. This activity aims to educate SDN 7 Mataram students about the importance of nutritious food in preventing stunting. The methods used in this activity are hands-on learning as well as fun learning interspersed with interesting games and pictures for students. Students are divided into groups and given the task of creating a project related to nutritious food. The project includes the creation of posters, papers, and presentations. The results of this activity showed that students showed increased knowledge and understanding of the importance of nutritious food in preventing stunting. Students also become more enthusiastic and creative in learning about nutrition. This activity is expected to contribute to stunting prevention efforts in Indonesia, especially in West Nusa Tenggara